Time for unorthodox monetary policy. - Muellbauer, J (CEPR, 2008)
This column explains the logic behind a radically new form of monetary policy – a new central-bank tool for stabilising the credit cycle. By buying bank stocks and credit instruments at the bottom of the cycle and selling at the top, the new policy could moderate the boom-and-bust credit cycle independently of interest rate policy. The Fed action on 25 November is a good step in this direction.